Analysis of Factors Affecting Employee Discipline The Covid-19 Pandemic Period at the Sinjai Regency DPRD Secretariat - Jamaluddin Jamaluddin; Riska Amelia; Risma Niswaty; Irwan Irwan (Pinisi Journal of Education and Management, 2022)
One of the most influential factors in human resources is the discipline factor. This study aims to determine the factors that influence employee discipline during the Covid-19 Pandemic at the Sinjai Regency DPRD Secretariat. This study uses a qualitative research method with 7 (seven) people, namely the leadership and employees of the DPRD secretariat. This research was conducted at the Secretariat of the DPRD Sinjai Regency. Data collection techniques by means of observation, interviews, and documentation. The data obtained from the research results are processed using data analysis techniques, namely data collection, data reduction, data presentation, conclusion/verification. The results show that the analysis of factors that influence employee discipline during the Covid-19 pandemic at the Sinjai Regency DPRD Secretariat proves that there are influencing factors, seen from the provision of employee compensation, leadership role models for employees, the existence of definite rules, leadership courage in taking action. , the existence of leadership supervision, and the establishment of discipline